2012
DOI: 10.3399/bjgp12x658304
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing long-term antidepressants can reduce drug burden: a prospective observational cohort study

Abstract: BackgroundAntidepressant prescribing continues to rise. Contributing factors are increased long-term prescribing and possibly the use of higher selective serotonin re-uptake inhibitor (SSRI) doses. AimTo review general practice patients prescribed the same antidepressant long-term (≥2 years) and evaluate prescribing and management pre and post-review. Design and settingProspective observational cohort study using routine data from 78 urban general practices, Scotland. MethodAll patients prescribed antidepressa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 23 publications
3
93
1
Order By: Relevance
“…Such use rose from 30.3% (1995-2005) to 43.7% (2005-2015). These findings are in line with those in other countries [12,25]. Our estimate of LTU may even be conservative for the Netherlands as a whole.…”
Section: Discussionsupporting
confidence: 81%
“…Such use rose from 30.3% (1995-2005) to 43.7% (2005-2015). These findings are in line with those in other countries [12,25]. Our estimate of LTU may even be conservative for the Netherlands as a whole.…”
Section: Discussionsupporting
confidence: 81%
“…Burton et al (2015) also found longer treatment duration was associated with diagnostic coding, which put patients into the QOF denominator for symptom questionnaire assessment at follow-up as well as diagnosis from 2009 onwards, suggesting the QOF might have increased duration of prescribing for QOF-qualifying cases. However, increased duration of prescribing predates the QOF , and surveys in the USA (where there is no QOF) as well as the UK have consistently found increasing long-term prescribing of antidepressants over the last 10 years, with more than half of patients being treated for two years or more, and a mean duration of treatment of between four and six years (Petty et al, 2006;Pratt et al, 2011;Johnson et al, 2012;Mojtabai and Olfson, 2014).…”
Section: Main Findings In Relation To Other Studiesmentioning
confidence: 96%
“…One large Scottish study using routine data from 78 urban general practices reported a mean length of use of 5.5 years (Johnson et al, 2012). Another US study found that around 60% of Americans taking antidepressant medication reported use for 2 years or longer, with 14% reporting use for 10 years or more (Pratt et al, 2011).…”
Section: Introductionmentioning
confidence: 95%